An International Comparative Study of Students' Scientific Explanation Based on Cognitive Diagnostic Assessment - Hu, Tao; Yang, Jing; Wu, Rongxiu; Wu, Xiaopeng (Frontiers in Psychology, 2021)
Scientific explanation is one of the most core concepts in science education, and its mastery level is crucial for a deep understanding of the nature of science. As a new generation of assessment theory, cognitive diagnostic assessment (CDA)can get the knowledge of students' mastery of fine-grained knowledge. Based on the existing research, this research has formed eight attributes of scientific interpretation. By coding the TIMSS test items, a cognitive diagnostic assessment tool was formed. Data collected from 574 Grade 4 students in Hangzhou, China, combined with the data of the United States, Singapore, Australia, the United Kingdom, and Russia were used in our study. The DINA model was used to analyze the results from three aspects: the probability of mastery of attributes, the international comparison of knowledge status, and the analysis of learning paths. This study provided a new perspective from CDA on the assessment of scientific ability